The Use of Slang Words in Instagram Posted by Billie Eilish - Anisa, Siti; Utomo, Slamet; rusiana, Rusiana (Universitas Muria Kudus, 2025)
The development of digital communication has significantly influenced language evolution, especially through social media platforms like Instagram. This study aims to identify the types of English slang words and analyze their functions in Billie Eilish’s Instagram posts. Using a qualitative descriptive method, the researcher collected and analyzed data from Billie Eilish’s Instagram captions posted between February 1st, 2024, and February 1st, 2025. The findings revealed that the types of slang used included clipping words, acronyms and initialisms, blended words, and metaphorical slang. These slang expressions served several communicative functions, such as emotional expression, identity expression, humor and playfulness, and efficiency in communication. Emotional expression was the most dominant function, showing Billie Eilish’s strategy to connect with her audience in a personal and relatable way. This study highlights that social media platforms not only facilitate linguistic creativity but also contribute significantly to the dissemination of slang among digital communities.